Occurrence data for stream-dwelling macroinvertebrates from Central EuropeGBIF-Global Biodiversity Information Facility - Dorottya Hárságyi; Balázs J. Berta; Bernadett Boóz; Zsuzsanna Pap; Bálint Pernecker; Anita Szloboda; Marko Miliša; Petr Pařil; Zoltán Csabai; Arnold Móra (Data in Brief)
Freshwater ecosystems represent an unparalleled diversity of habitats and species, but the actual distribution of many species remains obscured or incomplete. The aim of the survey was to contribute to the knowledge on the fauna of lesser-known areas and fill the gaps in the distribution maps of the species. The dataset is based on a one-year-long study surveying 60 locations from different drying river networks that represent different ecoregions in Central Europe: Balcanic (Croatia, 15 sites), Continental (Czechia, 20 sites) and Pannonian (Hungary, 25 sites). Multihabitat sampling approach was applied for collecting stream-dwelling macroinvertebrates. Individuals were identified to the lowest possible taxonomic level, typically to species level. The dataset includes 1827 geo-referenced occurrence records based on presence-absence data of 164 taxa across Gastropoda, Hirudinea and various groups of Insecta (Coleoptera, Hemiptera, Megaloptera, Odonata, Trichoptera) along with geographical information on the sampling sites, and details of the taxonomy of the species. The data can support future studies in ecology, biogeography and nature conservation.